Controls on lacustrine shale reservoir characteristics: insights from deposition, diagenesis, and geochemistry in the Jurassic Qianfoya Formation - Cheng, Lixue; Peng, Jun (Frontiers in Earth Science, 2025)
Continental lacustrine shales, which are distinct from marine shales in reservoir architecture, pose challenges for resource evaluation due to their complex multi-scale controls. The Middle Jurassic Qianfoya Formation in the Langzhong–Yuanba (LZ-YB) area of the northeastern Sichuan Basin represents a critical continental shale gas target, yet systematic studies of its reservoir quality drivers remain limited. Through integrated sedimentological, geochemical, and petrophysical analyses of core samples, three dominant sedimentary facies are identified: blocky, banded, and laminated, reflecting depositional energy variations. The formation shows favorable hydrocarbon potential with an average total organic carbon (TOC) content of 1.85% and is mineralogically dominated by clay minerals (illite and illite–smectite) and felsic components. Semi-deep lacustrine facies, especially clay-rich lithofacies, demonstrate superior reservoir quality due to higher total organic carbon content and pore networks dominated by silty intergranular pores, interlayer pores in clay minerals, and intragranular pores in pyrite and microfractures, contrasting with marine shales where organic matter-hosted pores prevail. Key controlling factors include organic matter-clay mineral synergy, depositional environment (anoxic conditions, freshwater influx, and terrigenous input), and diagenetic processes such as clay transformation and recompaction. Laminated facies exhibit optimal reservoir quality compared to blocky or banded types, with positive correlations between clay-organic content and storage capacity. These findings highlight the coupled depositional–diagenetic controls on continental shale reservoirs, providing critical insights for global exploration of analogous lacustrine shale systems.